Effective, convenient, and green sample preparation for the determination of retinol and retinol acetate in human serum using pipette tip microextraction - Suwanvecho, Chaweewan; Krčmová, Lenka Kujovská; Švec, František (Talanta, 2023)
An efficient sample preparation based on pipette tip microextraction that can be used for the analysis of retinol in human serum has been developed. Altogether, nine commercial pipette tips were compared based on recovery, sample volume, use of organic solvent, handling difficulty, duration of the preparation process, price, and greenness of the method. Retinol acetate was used as the internal standard. The extraction efficiency for both compounds was evaluated to optimize and select the best pipette tip for sample preparation, which was the WAX-S XTR pipette tip containing an ion exchanger and salt. This tip combined solid phase extraction and salting-out assisted liquid‒liquid extraction. Satisfying recoveries of 100 and 80% for retinol and retinol acetate, respectively, and good repeatability were demonstrated. The action of this pipette tip was based on the clean-up workflow in which the interferences were retained on the sorbent. The presence of residual interferences in the extracted samples did not affect the HPLC separation of compounds of interest. The simplicity of the clean-up workflow reduced the time of the sample preparation compared to the bind-wash-elute counterpart workflow. The advantages of our technique are its environmental friendliness and cost effectiveness. The selected pipette tip with an excellent microextraction efficiency enables sample preparation in both clinical research and practice.
Keywords: Solid Phase Extraction; Diterpenes; diterpeny; extrakce na pevné fázi; chlorid sodný; Vitamin A; vitamin A; Sodium Chloride; Retinyl Esters; Humans; lidé; retinylestery